A Speech Coder For PC Multimedia Net-To-Net Communication - Parvez, S (2020)
The paper presents a speech coding algorithm for operation at 11 025 samples/s. The coder provides improved speech quality and compatibility with the MS-Windows multimedia environment. The coding algorithm has been developed by adapting the ITU G729 and enhancing it with some recent developments in the medium band coding. The coder operates over a band of frequencies ranging from 20 to 5400 Hz at a bit rate of 8.9 kbit/s. Application of this coder includes intranet VoIP, voice chatting, multimedia communications, and voice archiving.